Myelin Water Imaging and Transcranial Magnetic Stimulation Suggest Structure-Function Relationships in Multiple Sclerosis - Zhao, Eric Y.; Vavasour, Irene M.; Zakeri, Marjan; Borich, Michael R.; Laule, Cornelia; Rauscher, Alexander; Traboulsee, Anthony; Li, David K. B.; Boyd, Lara A.; MacKay, Alex L. (Frontiers in Physics, 2019)
Demyelination can be assessed structurally by magnetic resonance imaging and functionally with transcranial magnetic stimulation. Here we combined these techniques to investigate demyelination of the corpus callosum in multiple sclerosis. Our objective was to determine if corpus callosal demyelination impacts transcallosal inhibition (TCI). TCI is a brief suppression of voluntary activity in the primary motor cortex elicited by stimulation of the homologous region of the contralateral hemisphere, which is assumed to be transmitted via the corpus callosum. Magnetic resonance imaging and transcranial magnetic stimulation were performed in 26 participants with MS and 10 controls. Myelin water fraction (MWF) was measured in five regions of the corpus callosum and compared with the onset latency, duration, and depth of TCI as measured by electromyography at the forearm. Callosal MWF was greatest posteriorly compared to other regions of the corpus callosum. Lower MWF in MS compared to controls was more pronounced in the posterior corpus callosum. MS participants had a prolonged TCI duration (p=0.016), which correlated with EDSS (p=0.020) and disease duration (p=0.045). In MS, TCI depth correlated negatively with the MWF of the posterior callosal midbody (p=0.039), a region thought to mediate TCI transmission. In summary, TCI duration was increased in MS and demyelination of the posterior corpus callosum midbody was associated with measurable functional changes. This work demonstrates the potential for combining magnetic resonance imaging and transcranial magnetic stimulation with electromyography to draw insights about structure-function relationships in MS pathophysiology.